Analysis of The Causes of Traffic Congestion (case study of jatiwangi—ligung road) - Mushthofa (LEADER: Civil Engineering and Architecture Journal, 2025)
Traffic congestion on Jatiwangi-Ligung Road in Majalengka Regency has become a major problem. The purpose of this study is to find out the causes of congestion and find the best way to solve it. This study found through field observations, traffic data analysis, and literature studies that the main causes of congestion are the increasing number of private vehicles, limited road capacity, and lack of public transportation integration. In addition, conventional markets and non-ideal intersections worsen traffic conditions. Based on these findings, this study recommends several strategies to overcome congestion, including: increasing road capacity, developing an integrated public transportation system, implementing a technology-based traffic management system, and consistent law enforcement. In addition, active community participation in efforts to reduce congestion is also very important. The results of this study are expected to be a basis for local governments in formulating more comprehensive and sustainable transportation policies, so that they can improve the quality of life of the community and reduce the negative impact of congestion on the local economy.